2021
DOI: 10.1021/acs.iecr.1c01636
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Kinetic Analysis of H2O on Hg0 Removal by Sorbent Traps in Oxy-combustion Atmosphere

Abstract: Oxy-combustion technology is under development for CO2 capture. H2O could influence the Hg0 removal by sorbent traps in an oxy-combustion atmosphere. A study of the effects of H2O on Hg0 removal by biomass char under oxy-combustion conditions is presented in this paper. The kinetic model analysis was conducted to study the adsorption process of Hg0, which included a pseudo-first-order kinetic model, a pseudo-second-order kinetic model, and intraparticle diffusion kinetic model. Experimental results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…TPD is a method of heating the desorption adsorbate according to a predetermined temperature program to obtain the relationship between the desorption amount and temperature. It is one of the most commonly used methods in our previous studies to explore the types of mercury compounds according to the different thermal stabilities of mercury compounds. …”
Section: Methodsmentioning
confidence: 99%
“…TPD is a method of heating the desorption adsorbate according to a predetermined temperature program to obtain the relationship between the desorption amount and temperature. It is one of the most commonly used methods in our previous studies to explore the types of mercury compounds according to the different thermal stabilities of mercury compounds. …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, NH 4 Br and HNO 3 are used for joint modification in this work, and the mercury removal mechanism is further analyzed. Wu 28 only studied the effect of H 2 O on the removal of Hg 0 from biomass char under the condition of oxy-fuel combustion, and the analysis of the effect on acid gas was not enough. In addition, in the oxy-fuel combustion flue gas, a complex atmosphere of acid gases such as SO 2 , HCl, and NO generally exists at the same time.…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 Biomass char is an ideal adsorbent for mercury removal due to its low price, abundant surface functional groups, simple raw materials, and environmental protection. 31 , 32 …”
Section: Introductionmentioning
confidence: 99%
“…29,30 Biomass char is an ideal adsorbent for mercury removal due to its low price, abundant surface functional groups, simple raw materials, and environmental protection. 31,32 The parameters in the experiment will also have a great impact on the experimental results. Zhao et al 33 showed that the change of Hg 0 removal efficiency with the increase of reaction temperature is non-monotonical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation